2021
DOI: 10.1556/2060.2021.00018
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hyperbilirubinemia: Background and recent literature updates on the diagnosis and treatment

Abstract: Hyperbilirubinemia or jaundice has been studied by many researchers because of its diverse causes and potential for toxicity especially in the neonate but to a lesser extent beyond the neonate as well. Several studies have been performed on the normal metabolism and metabolic disorders of bilirubin in last decades of the 20th century. The recent advancement in research and technology facilitated for the researchers to investigate new horizons of the causes and treatment of neonatal hyperbilirubinemia. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Neonatal jaundice is mostly due to unconjugated hyperbilirubinaemia and very common occurring in 50% of full-term and 84% near-term neonates 4. Neonates are susceptible because their red blood cells (RBCs) have a reduced life span of 60–90 days, there is increased degradation of haem, and they have only 1% of adult levels of the liver enzyme uridine 5′-diphosphoglucuronosyltransferase (UGT1A1 responsible for bilirubin conjugation) 5 6…”
Section: Case: Tailing Growth and Neonatal Jaundicementioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal jaundice is mostly due to unconjugated hyperbilirubinaemia and very common occurring in 50% of full-term and 84% near-term neonates 4. Neonates are susceptible because their red blood cells (RBCs) have a reduced life span of 60–90 days, there is increased degradation of haem, and they have only 1% of adult levels of the liver enzyme uridine 5′-diphosphoglucuronosyltransferase (UGT1A1 responsible for bilirubin conjugation) 5 6…”
Section: Case: Tailing Growth and Neonatal Jaundicementioning
confidence: 99%
“…Common but pathological causes are haemolysis due to rhesus or ABO incompatibility, polycythaemia and sepsis. Any condition impacting the bilirubin pathway can lead to jaundice: increased extravascular blood, abnormal haemolysis, impaired bilirubin transport, impaired liver uptake, impaired conjugation and impaired excretion 6. Causes include haematological, endocrine and metabolic conditions (table 2).…”
Section: Case: Tailing Growth and Neonatal Jaundicementioning
confidence: 99%
“…Recently, massage therapy has been introduced as a new and effective method in the treatment of newborns with jaundice [120]. Shahbazi et al showed that the average bilirubin levels decreased as the level of massage intervention (i.e., massage duration and frequency per minute) increased.…”
Section: Massagementioning
confidence: 99%
“…Without timely diagnosis and treatment, bilirubin can traverse the blood-brain barrier trigger bilirubin encephalopathy and lead to long-term complications. In severe cases, it may even result in fatality (3)(4)(5)(6). NHB and its subsequent condition, bilirubin encephalopathy, have consistently posed a significant disease burden worldwide (7,8).…”
Section: Introductionmentioning
confidence: 99%